2022
DOI: 10.1016/j.jbc.2021.101471
|View full text |Cite
|
Sign up to set email alerts
|

The double lives of phosphatases of regenerating liver: A structural view of their catalytic and noncatalytic activities

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 96 publications
0
10
0
Order By: Relevance
“…Examples of enzymes which moonlight to also perform nonenzymatic functions are known. One example is the phosphatase of regenerating liver (PRL), which has catalytic phosphatase activity for certain phosphorylated substrates but also has a non-catalytic role in regulating the integral membrane magnesium transporter CNNM ( 58 , 59 ). Structural analyses revealed that CNNM mimics a PRL substrate and binds near residues in PRL required for catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of enzymes which moonlight to also perform nonenzymatic functions are known. One example is the phosphatase of regenerating liver (PRL), which has catalytic phosphatase activity for certain phosphorylated substrates but also has a non-catalytic role in regulating the integral membrane magnesium transporter CNNM ( 58 , 59 ). Structural analyses revealed that CNNM mimics a PRL substrate and binds near residues in PRL required for catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to ARL15, CNNM CBS-pair domains bind PRLs with low nanomolar affinity (Gulerez et al ., 2016). Binding is mediated by an aspartic acid that inserts into the phosphatase catalytic site, mimicking a phosphoprotein substrate (Gehring et al, 2022; Gimenez-Mascarell et al ., 2017; Gulerez et al ., 2016). While the binding sites overlap, a CNNM dimer could simultaneously bind ARL15 and PRLs using separate CBS-pair domains.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their broad distribution and importance in cancer and development, PRLs are poorly understood ( 15 ). They are highly potent oncogenes implicated in tumorigenesis and metastasis but have no confirmed substrates.…”
Section: Discussionmentioning
confidence: 99%
“…A phosphorous-sulfur intermediate occurs in all cysteine-based phosphatases ( 11 , 12 ), but the intermediate is unusually long-lived in PRLs ( 10 , 13 , 14 ). The accumulation of phosphorylated enzyme leads to the phenomenon of burst kinetics, which is characterized by a fast initial rate of catalysis followed by a slow steady-state rate ( 10 , 15 ). In cells, PRLs are largely found in the phosphorylated form and the level of phosphorylation varies as a function of magnesium availability ( 13 , 14 ).…”
mentioning
confidence: 99%